2019
DOI: 10.1097/md.0000000000017436
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenems vs tigecycline for the treatment of complicated intra-abdominal infections

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
(56 reference statements)
2
3
0
Order By: Relevance
“…From the point of this view, both tigecycline and meropenem are feasible in the treatment of postoperative cIAIs of abdominal tumor patients. A Bayesian network meta-analysis of randomized clinical trials showed that on differences in clinical and microbiological outcomes and mortality observed between meropenem and tigecycline (21), which supported our conclusion.…”
Section: Discussionsupporting
confidence: 85%
“…From the point of this view, both tigecycline and meropenem are feasible in the treatment of postoperative cIAIs of abdominal tumor patients. A Bayesian network meta-analysis of randomized clinical trials showed that on differences in clinical and microbiological outcomes and mortality observed between meropenem and tigecycline (21), which supported our conclusion.…”
Section: Discussionsupporting
confidence: 85%
“…The comparison of carbapenems and tigecycline in our pairwise meta-analysis was of borderline signi cance, but no signi cant difference was observed in the NMA. A Bayesian metaanalysis of 15 studies comparing the effectiveness of individual carbapenems versus tigecycline showed consistent results (29). Thus, the borderline signi cance result in our study should be interpreted conservatively (30).…”
Section: Discussionsupporting
confidence: 54%
“…Our ndings re ect the real-time and supplementary evidence regarding the e cacy and safety of tigecycline compared with other regimens for cIAI treatment. Indeed, other studies have shown higher rates of adverse events in patients treated with tigecycline relative to those treated with comparators (29,33). Nevertheless, tigecycline remains an important treatment option for patients suspected of have an infection with an antibiotic-resistant pathogen (1,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings reflect real-time and supplementary evidence regarding the efficacy and safety of tigecycline compared with other regimens for cIAI treatment. Indeed, other studies have shown higher rates of AEs in patients treated with tigecycline relative to other treatments[ 32 , 33 ]. Nevertheless, tigecycline remains an important treatment option for patients suspected of being infected with an antibiotic-resistant pathogen [ 1 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%